Un anno di Leggere: Forte! in Toscana L'esperienza di una ricerca-azione - Batini, Federico (Storie per le persone e le comunità, 2021)
Reading aloud represents one of the most effective practices for cognitive democracy that schools can adopt to guarantee academic success for all children and youth. With the multi-year project "Reading: So Cool!", the Region of Tuscany wanted to introduce reading aloud in early childhood education services and schools in a systematic and structured way. The aim was to promote reading aloud as a regular and daily practice for the entire education system in Tuscany to reduce, over time, school dropout and learning inequalities. Starting from experience in the field, this book recounts, documents and explains the intentions, actions and results of the first year of activity in this project. It shares the theoretical foundations, practices, evidence collected and results achieved without forgetting the difficulties and a critical assessment. The dissemination of this experience is important and allows the promotion and replication - including outside the Tuscan region - the aims and tools of what has become, over time, a real educational policy that is able to encourage the achievement of core skills not only at school, but for life.